Pengaruh Iklan Televisi Nutrisari Versi Si Juara Nyegerin terhadap Keputusan Pembelian Produk : Survey pada Warga komplek Graha Indah 2 Pamulang - Denny Wahyudi; Agus Hermanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
In the increasingly tight competition of the soft drink industry, companies need to understand how the advertisements broadcast are able to attract attention, arouse interest, and encourage consumers to make purchases. The purpose of this study is to measure 1) The television advertisement of Nutrisari version of the champion nyegerin on residents of the Graha Indah 2 Pamulang complex. 2) Purchasing decisions on residents of the Graha Indah 2 Pamulang complex. 3) The influence of the television advertisement of Nutrisari version of the champion nyegerin on product purchasing decisions on residents of the Graha Indah 2 Pamulang complex. The theory used in this study is the Marketing Communication Theory. Television Advertisements with dimensions: Head words & sound effect, Music, Seen word, Picture, Color, and Movement, as well as the Purchasing Decision theory with dimensions: Problem Recognition, Information Search, Alternative Evaluation, Purchase Decision, and Post-Purchase Behavior. This study uses a quantitative approach with a survey method with a questionnaire as the data collection instrument. The population in this study were residents of the Graha Indah 2 Pamulang RW 25 complex with characteristics that had been found as many as 123 and the number of samples as many as 94. The sampling technique used probability sampling technique. The results of the study showed that 1) The images presented in Nutrisari advertisements made the audience's attention interesting and got the highest average value of 3.28 from the Picture dimension. 2) In the Purchase Decision, there was the highest value of 3.21 from the Purchase Decision dimension. 3) There was an Influence of Nutrisari Television Advertisement Version of Si Juara Nyegerin on Product Purchase Decisions. t-count was (9.992) > t-table (1.661). The magnitude of the influence was R 0.719 or 71.9% and R Square was 0.517 or 51.7%